2020
DOI: 10.1111/fcp.12543
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hydrogen sulfide alleviates methotrexate‐induced cognitive impairment by attenuating endoplasmic reticulum stress‐induced apoptosis via CHOP and caspase‐12

Abstract: The aim of this study was to estimate whether methotrexate (MTX) promotes cognitive impairment via increased ER stress and disrupted H2S signaling in the hippocampus and whether H2S may alleviate MTX‐induced cognitive impairment by inhibiting ER stress through CHOP and caspase‐12. Cognitive impairment behaviors were observed by Morris water maze test, and the apoptosis of neurons was assessed by TUNEL assay. The production of neurons was analyzed by DCX and Ki67 immunohistochemistry. The expressions of CHOP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In the hippocampus, MTX increased the expression of CHOP (CCAAT/enhancer-binding protein (C/EBP)-homologous protein) and cleaved caspase 12 and decreased the expression of DCX-and Ki67-positive neurons in the dentate gyrus. Spatial memory impairments were assessed in the same study using MWM, where the rats with MTX showed a significant decrease in the time spent in the target quadrant compared to the vehicle-treated group (Lv et al 2020). Five-week-old Sprague-Dawley rats when treated with MTX (75 mg/kg, i.v) induced changes in hippocampal neurogenesis and behavioral parameters shown by memory deficits in NORT and OLT shown by decrease in preference index as well as decline in neurogenesis markers like Ki67-, BrdU-, and DCX-positive cells (Naewla et al 2019).…”
Section: Methotrexatementioning
confidence: 99%
“…In the hippocampus, MTX increased the expression of CHOP (CCAAT/enhancer-binding protein (C/EBP)-homologous protein) and cleaved caspase 12 and decreased the expression of DCX-and Ki67-positive neurons in the dentate gyrus. Spatial memory impairments were assessed in the same study using MWM, where the rats with MTX showed a significant decrease in the time spent in the target quadrant compared to the vehicle-treated group (Lv et al 2020). Five-week-old Sprague-Dawley rats when treated with MTX (75 mg/kg, i.v) induced changes in hippocampal neurogenesis and behavioral parameters shown by memory deficits in NORT and OLT shown by decrease in preference index as well as decline in neurogenesis markers like Ki67-, BrdU-, and DCX-positive cells (Naewla et al 2019).…”
Section: Methotrexatementioning
confidence: 99%
“…Considering these, possible candidates for the mechanism of action of H 2 S may be those (relatively early) cellular effectors or processes that regulate the activation of the three main proximal effectors of UPR (PERK, IRE1α, and ATF6) that are common to both calcium-dependent and -independent triggers of ER stress. Multiple prior reports in the literature have indicated that H 2 S donation can ameliorate various ER-stress-related downstream parameters (in signaling and/or in cellular bioenergetics or viability) [57][58][59][60][61][62][63][64][65]. However, the exact molecular site(s) of the beneficial action of H 2 S on the initiation and progression of ER stress and ER-stress-associated cellular responses remain to be further refined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been maintained that H 2 S donors, which have shown protective effects from mitochondrial dysfunction and oxidative damage, may be beneficial in AD 121 . In another study, it was reported that hippocampal H 2 S production decreased in cognitive impairment induced by methotrexate, and exogenous H 2 S treatment (NaHS) alleviated cognitive impairment by both increasing the decreased H 2 S levels and reducing endoplasmic reticulum stress 122 . Memantine was combined with ferulic acid, which is known to protect the brain against Aβ neurotoxicity and ROS, and it was revealed that one of the hybrid substances may be beneficial with its antioxidant effect in cases of NMDA receptor‐mediated neurotoxicity involving oxidative stress such as AD 123 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…121 In another study, it was reported that hippocampal H 2 S production decreased in cognitive impairment induced by methotrexate, and exogenous H 2 S treatment (NaHS) alleviated cognitive impairment by both increasing the decreased H 2 S levels and reducing endoplasmic reticulum stress. 122 Memantine was combined with ferulic acid, which is known to protect the brain against Aβ neurotoxicity and ROS, and it was revealed that one of the hybrid substances may be beneficial with its antioxidant effect in cases of NMDA receptor-mediated neurotoxicity involving oxidative stress such as AD. 123 In recent years, it has been proposed that yttrium in the form of nanoparticles (nanoyttria) may be useful in the treatment of AD with its antioxidant effects 124 (Table 1).…”
Section: Oxidative Stressmentioning
confidence: 99%